Neck muscular strength, training, performance and sport injury risk: A review - Hrysomallis, C. (Sports Medicine, 2016)
The neck musculature has an essential role in positioning and stabilising the head and may influence sport performance and injury risk. The objectives of this review are to (1) compare the neck strength of different athletes; (2) report on the outcomes of training programmes; (3) explore the association between neck strength and head stabilisation; (4) examine the relationship between neck strength and sport injury risk; and (5) identify areas for future research. There was a difference in strength between different player positions in football codes, gender and age. Detected differences were partly attributed to variation in neck muscle mass. Neck strength training programmes were generally shown to be effective for untrained and trained participants using dynamic or isometric actions and various types of resistance devices. There was a wide range of reported increases in neck strength; the smallest gains were usually for programmes that utilised lower intensity or frequency. There was limited evidence that greater isometric strength or dynamic training was associated with better head stabilisation during low-level force application, while there is direct evidence of an association between neck isometric training or strength and injury risk. A retrospective analysis of professional rugby union players revealed that isometric training reduced match-related cervical spine injuries and a prospective study found that greater overall isometric neck strength reduced concussion risk in high school athletes. Recommendations for future research include substantiating the link between neck strength and sport injury risk and assessing the effectiveness of neck plyometric and perturbation training on stabilisation and injury risk.